HARTA DALAM KONSEPSI ADAT MINANGKABAU - Haron, Mohammad Sabri bin; Hanifuddin, Iza (Faculty of Shariah of State Institute for Islamic Studies Batusangkar, Indonesia, 2012)
Minangkabau, with all of its aspects, has attracted academician to conduct researches about it. In terms of wealth, this tribe has a great detailed concepts. Comprehensive descriptions upon wealth center around the systems of kinship, power, and land ownership which is known as suku, sako and pusako. Social value of wealth is realized through communal wealth ownership. The authority of wealth is socialized by presenting tribal address to other people through the concept of sasongko. This wealth is supposed to inherit from generation to generation by means of communal authority system. However, some external systems, such as Islam, have given fundamental change which is considered too intervening. Consequently, the community cannot fully accept the change but, in other hand, do not want to reject it.